Socio-Cultural Changes in the Functioning of the Ukrainian Language in Ukraine in 2014–2024 - Nina Danylyuk; Oksana Rohach (Slavia Meridionalis, 2025)
The article traces socio-cultural changes in the functioning of the Ukrainian language in Ukraine in 2014–2024 on the basis of legislative documents, works of scholars, articles in the media, and the results of monitoring and sociological surveys. It was found that due to the language policy of the state, the communicative prestige of the Ukrainian language in the state and public spheres has increased. In private communication, the language has spread as a result of the growth of the national and linguistic consciousness of Ukrainians, as well as their ethnic and state selfidentification. During the ethno-socio-political challenges, the functions of (self-)identification, consolidation, national-cultural, nation- and state-building have been actualized. During the war, the Ukrainian language has begun to perform special functions: it has became a symbol of independence and a means of national security, struggle and resistance against enemy aggression.